Medical ethics and the clinical curriculum: a case study - Doyal, L. (Journal of medical ethics, 1987)
There are very few medical ethics courses in British medical schools which are a formal part of the clinical curriculum. Such a programme is described in the following, along with the way in which the long-term curriculum committee of the University College and Middlesex Hospital Joint Medical School was persuaded to make it compulsory for first-year students. Pedagogical lessons which have been learned in its planning and implementation are outlined and teaching materials are included concerning student and course assessment which should be useful for others engaged in similar work. Finally, some of the institutional obstacles facing such attempts are discussed, particularly problems concerning timetabling, different types of opposition and the consequent importance of building alliances among clinical teaching staff.